ANALISIS FISIKO-KIMIA SIMPLISIA DAN PROFIL KROMATOGRAFI LAPIS TIPIS HERBA BANDOTAN (Ageratum conyzoides L.) - Pratimasari, Diah; Disa Andriani (BENZENA Pharmaceutical Scientific Journal, 2025)
Background: Bandotan plant (Ageratum conyzoides L.) is a plant of the Aceraceae family that grows wild. Bandotan is empirically used as an antiseptic and wound healer. In addition, bandotan plants are also reported to have activities as antipyretic, anti-inflammatory, and antioxidant. These various pharmacological activities make the bandotan plant potential to be developed as a medicinal and cosmetic raw material. So far, research related to bandotan standardization has been carried out on the leaves, even though all parts of the bandotan plant including the roots have the potential to be developed. In addition, the use of all parts of the plant supports green chemistry, namely minimizing residual production waste. Objective: This study aims to conduct chemical physicochemical characterization of simplisia of all parts of bandotan herb and its Thin Layer Chromatography (TLC) profile. Methods: This research begins with making simplisia from all parts of the bandotan plant. The obtained simplisia was then observed for its physicochemical aspects including drying shrinkage, total ash content, water soluble juice content, ethanol soluble juice content and TLC identification. In addition to making simplisia, all parts of bandotan were also extracted with 70% ethanol, to be analyzed KLT compared with simplisia and kaemferol standards. Conclusion: The use of all parts of the bandotan herb plant meets the quality standards of simplisia. In addition, the use of all parts of the plant shows a diversity of spots on KLT that have the potential to be developed as medicinal and cosmetic raw materials